2017
DOI: 10.2217/fon-2017-0336
|View full text |Cite|
|
Sign up to set email alerts
|

Ado-Trastuzumab Emtansine (T-DM1) in HER2+ Advanced Breast Cancer Patients: does Pretreatment with Pertuzumab Matter?

Abstract: Patients treated with T-DM1 who previously received pertuzumab present poorer clinical outcomes compared with those receiving a trastuzumab-only-based regimen in the first-line setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 12 publications
3
22
1
Order By: Relevance
“…However, other real-world studies have suggested inferior outcomes for patients treated with TE after pertuzumab exposure compared with pertuzumab-naïve patients. In a study by Fabi et al, 27 34 patients with prior trastuzumab/pertuzumab had significantly worse PFS compared with 73 patients with prior trastuzumab only (5 vs 11 months). In a multicenter, Italian cohort of 250 patients, PFS and OS were numerically less for patients with prior trastuzumab/pertuzumab in comparison to patients with prior trastuzumab only.…”
Section: Discussionmentioning
confidence: 95%
“…However, other real-world studies have suggested inferior outcomes for patients treated with TE after pertuzumab exposure compared with pertuzumab-naïve patients. In a study by Fabi et al, 27 34 patients with prior trastuzumab/pertuzumab had significantly worse PFS compared with 73 patients with prior trastuzumab only (5 vs 11 months). In a multicenter, Italian cohort of 250 patients, PFS and OS were numerically less for patients with prior trastuzumab/pertuzumab in comparison to patients with prior trastuzumab only.…”
Section: Discussionmentioning
confidence: 95%
“…There were two other retrospective studies conducted in Italy, which compared PFS of T-DM1 between patients who had received Pmab and those without Pmab exposure [ 13 , 14 ]. They also showed the shorter duration of PFS in patients who had received Pmab in second line treatment (3 months [95% CI 2–4 months] vs. 8 months [95% CI 4–12 months] [ 13 ] and 5.0 months [95% CI 4.3–5.7 months] vs. 11.0 months [95% CI 7.8–14.2 months] [ 14 ]).…”
Section: Discussionmentioning
confidence: 99%
“…There were two other retrospective studies conducted in Italy, which compared PFS of T-DM1 between patients who had received Pmab and those without Pmab exposure [ 13 , 14 ]. They also showed the shorter duration of PFS in patients who had received Pmab in second line treatment (3 months [95% CI 2–4 months] vs. 8 months [95% CI 4–12 months] [ 13 ] and 5.0 months [95% CI 4.3–5.7 months] vs. 11.0 months [95% CI 7.8–14.2 months] [ 14 ]). The study reported by Fabi et al [ 14 ] provided propensity score-matched sample with perfect match for age and PFS at first-line, and it also showed a shorter PFS in patients treated with Pmab (5.0 months [95% CI 4.3–5.7 months] vs. 11.0 months [95% CI 7.3–14.0 months]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In post hoc analysis of T-DXd, previous pertuzumab use did not affect the results either [17]. But the possibility that treatment after pertuzumab can be less effective has been suggested [18][19][20], though it was based on small and observational studies examining the efficacy of T-DM1 in patients with previous pertuzumab. Thus, further investigation is warranted to evaluate the influence of previous pertuzumab use over post-T-DM1 treatment.…”
Section: Discussionmentioning
confidence: 99%